Task-based language learning and teaching: An action-research study - Calvert, Megan; Sheen, Younghee (Language teaching research : LTR, 2015)
The creation, implementation, and evaluation of language learning tasks remain a challenge for many teachers, especially those with limited experience with using tasks in their teaching. This action-research study reports on one teacher’s experience of developing, implementing, critically reflecting on, and modifying a language learning task to better address the needs of her students in an adult refugee English program. Task evaluation involved a response-based comparison of student success in task completion and qualitative student-based results. The results noticeably improved after the task modification and the successful implementation of the modified task led to changes in how the teacher viewed task-based teaching. The study serves as an example of how teachers can create their own tasks and of the importance of evaluating them empirically. The article concludes with the importance of action research as a means by which language teachers can address problems that arise in task-based instruction.